Effect of Integrated Nutrient Management (INM) on Growth, Yield and Quality of Maize (Zea mays L.) - Saini, Shivam; Singh, Satybhan; Singh, Virendra (Journal of Neonatal Surgery, 2025)
A field experiment was conducted to evaluate the effect of integrated nutrient management (INM) on growth, yield and quality of maize. The study was carried out at the agronomy research farm of IFTM University, Moradabad, Uttar Pradesh, India during the kharif season of 2023 and 2024. Twelve treatments comprising varying combinations of recommended doses of fertilizers with organic sources such as biogas slurry, vermicompost, farmyard manure, poultry manure, and green manuring with Sesbania spp. were evaluated in randomized block design (RBD) and replicated thrice. Maize variety VHM-53 was planted with 50 × 20 cm spacing. The soil of experimental field was clay loam. Recommended dose of fertilizers (RDF) was used @ 120: 60: 40 kg/ha. Results revealed that different levels of nutrients and organic manures significantly improved the growth, yield attributes, yield and quality parameters of maize. Highest grain yield was recorded with T9 (75 % RDF + 25 % N through Poultry manure) in which significantly increased all growth attributes viz., plant height, leaf area index and dry weight, as well as on yield attributing characters such as number of cobs/plant, number of grains/cob, seed index g. Maximum grain yield (5.28 and 5.30 t/ha) was recorded in T9 which was significantly highest over rest of the treatments. Protein content (12.16 % and 12.33 %) and protein yield (642.04 kg and 653.13 kg/ha) was also highest in T9 which was significantly higher over rest of the treatments